Experimental substantiation of a combination of structural materials and personalized prosthetic elements for prosthetics on dental implants - Leonenko П. В.; Kokoyeva Ю. В. (Actual Dentistry, 2020)
Summary. From literature data it is known that the long-term success of dental implantation depends not only on careful planning and surgical intervention in compliance with the protocol requirements, but also on the type of load on the dental implants, which significantly depends on the design features of the prostheses that are fixed on them. The presence of a significant number of proposals of structural materials on the Ukrainian market for the manufacture of dental prostheses at the prosthetic stage disorients doctors and dental technicians, who in most cases choose them empirically. The finite element method allows conducting preclinical studies and experimentally select the most effective personalized structural solutions for prosthetics on dental implants, as well as structural materials or a combination for their manufacture in order to optimize the load on the implant and bone tissue. Purpose: substantiate combinations of structural materials and personalized prosthetic elements for prosthetics on dental implants by studying the stress-strain state in simulation models "bone tissue – dental implant – prosthetic element – personalized abutment – supraconstruction”. Materials and methods. The experimental study was carried out on multidimensional simulation models “bone tissue – dental implant – prosthetic element – personalized abutment – suprastructure”. They had stable physical and mechanical properties of bone tissue, dental implants and standard prosthetic elements and their loading conditions, and differed in the types of structural materials from which personalized abutments and suprastructures were made. The basic types of models contained – T1 personalized abutment made of polyetheretherketone (PEEK), as well as T2 personalized abutment made of zirconium dioxide. In the study, the basic types of simulation models were combined with various types of suprastructures made of: lithium disilicate glass ceramic (K1); composite modified hybrid ceramics (K2); polymethyl methacrylate PMMA (K3); multilayer zirconium dioxide (K4). Results. During the numerical analysis of the stress-strain state of the biomechanical systems “bone tissue – dental implant – prosthetic element – personalized abutment – suprastructure” it was found that the most loaded elements of the system were: suprastructure (143.57 MPa – in the model with T1 type of personalized abutment; 156.25 MPa – in the model with T2 type of personalized abutment); spongy (3.84 MPa – with T1 type of personalized abutment; 3.36 MPa – with T2 type of personalized abutment) and cortical bone tissue (18.67 MPa – with T1 type of personalized abutment; 16.46 MPa – with T2 type of personalized abutment), with the corresponding indicators of safety factors for each of these elements. Biomechanical systems with T1 and T2 personalized abutments have the greatest bearing capacity when using superstructure materials: K1 (minimum safety factor – 2.10 in the model with T1 type of personalized abutment; minimum safety factor – 2.29 in the model with T2 type of personalized abutment) and K4 (minimum safety factor – 2.08 in the model with T1 type of personalized abutment; minimum safety factor – 2.38 in the model with T2 type of personalized abutment). When using materials of crown K2 (minimum safety factor – 0.86 in the model with T1 type of personalized abutment; minimum safety factor – 0.79 in the model with T2 type of personalized abutment) and K3 (minimum safety factor – 0.98 in the model with T1 type of personalized abutment; minimum safety factor – in a model with a T2 type of personalized abutment) biomechanical systems had a lower bearing capacity. In the study of models with T1 personalized abutment, an increase of 1.63–4.57 times the maximum von Mises stress in the abutment was noted, compared the maximum von Mises stress equivalent in the abutment of models with T2 personalized abutment. Conclusions. It is scientifically substantiated that there is a significant effect of various combinations of the mechanical properties of structural materials for the manufacture of personalized abutments and prostheses on the general stress-strain state of all elements of the biomechanical system “bone tissue – dental implant – prosthetic element – personalized abutment – suprastructure” in general. For the first time, the optimal combination of structural materials for the manufacture of personalized abutments and dentures for direct prosthetics on dental implants has been scientifically substantiated. According to the results of the analysis of the values of the von Mises stresses equivalent and safety factors, the recommended material for the manufacture of personalized abutment on a standard titanium platform is zirconium dioxide (safety factor – 30.28), which in combination with a crown made of lithium disilicate glass ceramic (safety factor – 2.29) or multilayered translucent zirconium dioxide (safety factor – 5.22), reliably better (p < 0.05) redistribute concentrated point functional loads and provide better biomechanical stability of the whole system. According to the results of experimental studies of stress-strain states of all elements of the biomechanical system “bone tissue – dental implant – prosthetic element – personalized abutment – suprastructure” the worst option for manufacturing personalized abutments on standard titanium platforms is PEEK structural material.